2004
DOI: 10.1111/j.1468-8123.2004.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Massive dolomitization of a Messinian reef in the Great Bahama Bank: a numerical modelling evaluation of Kohout geothermal convection

Abstract: The hypothesis that Kohout thermal convection may have induced the massive dolomitization of the 60 m thick lowest more reefal unit in well Unda [top of Great Bahama Bank (GBB)] is evaluated through numerical modelling. A twodimensional (2-D) section, including lithological and petrophysical data, together with datings for the sediments of the GBB, was used in the basin model TEMISPACK to reconstruct the history of the whole platform, with a focus on the reef unit.Simulations showed that during high sea-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
(82 reference statements)
3
19
0
Order By: Relevance
“…Following Caspard et al (2004), we calculate the time for complete dolomitization by assuming that (1) dolomitization occurs as a replacement process, and (2) dolomitization is limited by seawater infl ow rates and seawater Mg molarity (0.045 mol/L). For the geometry of our case, we further assume that (3) the axis of the predevelop- on August 20, 2015 geology.gsapubs.org Downloaded from ment Upper Floridan aquifer potentiometric surface (Fig.…”
Section: Implications Of the Effect Of Heat Flow On Dolomitization Timementioning
confidence: 99%
See 1 more Smart Citation
“…Following Caspard et al (2004), we calculate the time for complete dolomitization by assuming that (1) dolomitization occurs as a replacement process, and (2) dolomitization is limited by seawater infl ow rates and seawater Mg molarity (0.045 mol/L). For the geometry of our case, we further assume that (3) the axis of the predevelop- on August 20, 2015 geology.gsapubs.org Downloaded from ment Upper Floridan aquifer potentiometric surface (Fig.…”
Section: Implications Of the Effect Of Heat Flow On Dolomitization Timementioning
confidence: 99%
“…This type of convection has been invoked as a conceptual model for dolomitization in numerous modern carbonate platforms, including the Bahamas (Whitaker et al, 1994;Caspard et al, 2004), Enewetak Atoll (Saller, 1984), Mururoa (Buigues, 1997), French Polynesia (Rougerie et al, 1997), and other atolls (Leclerc et al, 1999). Numerical simulation of two-dimensional (2-D) fl ow in generalized carbonate platforms has suggested that geothermal heat fl ow can cause convective circulation to depths of several kilometers (e.g., Kohout et al, 1977;Sanford et al, 1998;Wilson et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…The absence of aragonite needles at the proximal part of the slope implies granulometric sorting. Previous authors, however, postulated that pore fluid circulation inside the bank is preferentially active in permeable sediments in the slope domain (Eberli et al 1997;Caspard et al 2004). For this reason, the absence of needles in the proximal sites is certainly enhanced by aragonite dissolution processes resulting in precipitation of diagenetically more stable authigenic carbonates.…”
Section: Aragonite Needles: Precipitation Sitementioning
confidence: 92%
“…Yet, horizontal flow is appropriate because it prevails over large portions of nearly all larger‐scale dolomite RTMs. Streamlines are dominantly horizontal for tens of kilometres with geothermal circulation in stratified carbonates (Caspard et al ., ; Whitaker & Xiao, ). Models of compaction‐driven flow or hot fluids injected from faults into layered limestones all exhibit horizontal flow due to permeability differences between layers (Consonni et al ., ; Xiao et al ., ; Corbella et al ., ; Lu & Cantrell, ).…”
Section: Methodsmentioning
confidence: 99%